2009
DOI: 10.1103/physreva.80.032111
|View full text |Cite
|
Sign up to set email alerts
|

Decoherence due to an excited-state quantum phase transition in a two-level boson model

Abstract: The decoherence induced on a single qubit by its interaction with the environment is studied. The environment is modeled as a scalar two-level boson system that can go through either first-order or continuousexcited-state quantum phase transitions, depending on the values of the control parameters. A mean-field method based on the Tamm-Damkoff approximation is worked out in order to understand the observed behavior of the decoherence. Only the continuous-excited-state phase transition produces a noticeable eff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
102
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(104 citation statements)
references
References 21 publications
(38 reference statements)
1
102
0
Order By: Relevance
“…Typical examples are the U(5)-SO(6) ESQPT [9][10][11] in the IBM and the U(2)-SO(3) ESQPT [15,16] in the two dimensional limit of the VM. ESQPTs in other many-body quantum systems have also been investigated, such as those in the Lipkin-Meshkov-Glick (LMG) model [20,21], the Jaynes-Cummings model [22,23], the Dicke model [22][23][24], and the kicked-top model [25]. Generally, ESQPTs emerge in the systems with a large number of particles.…”
Section: Introductionmentioning
confidence: 99%
“…Typical examples are the U(5)-SO(6) ESQPT [9][10][11] in the IBM and the U(2)-SO(3) ESQPT [15,16] in the two dimensional limit of the VM. ESQPTs in other many-body quantum systems have also been investigated, such as those in the Lipkin-Meshkov-Glick (LMG) model [20,21], the Jaynes-Cummings model [22,23], the Dicke model [22][23][24], and the kicked-top model [25]. Generally, ESQPTs emerge in the systems with a large number of particles.…”
Section: Introductionmentioning
confidence: 99%
“…This critical point can be reached either for a constant excited energy by varying the control parameter(s) or by fixing the latter and increasing the energy. ESQPTs have been investigated for a broad class of many-body quantum systems, such as the Lipkin-Meshkov-Glick (LMG) [17][18][19], the molecular vibron [15,20] In terms of dynamics, it has been shown that an ESQPT leads to random oscillations of the survival probability in isolated systems [21], to singularities in the evolution of observables [32], and to maximal decoherence in open systems [18,33]. Despite these works, studies of the effects of ESQPTs on systems' evolutions are still scarce.…”
mentioning
confidence: 99%
“…In terms of dynamics, it has been shown that an ESQPT leads to random oscillations of the survival probability in isolated systems [21], to singularities in the evolution of observables [32], and to maximal decoherence in open systems [18,33]. Despite these works, studies of the effects of ESQPTs on systems' evolutions are still scarce.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This divergence in the density states at the lowest energy moves to higher energies as the control parameter increases above the QPT critical point. The energy value where the density of states peaks marks the point of the ESQPT.ESQPTs have been analyzed in various theoretical models [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] and have also been observed experimentally [22][23][24][25][26][27]. They have been linked with the bifurcation phenomenon [20] and with the exceedingly slow evolution of initial states with energy close to the ESQPT critical point [18][19][20].…”
mentioning
confidence: 99%